THEORETICAL BASIS OF THE TRAIL MAKING TEST (TMT) METHODOLOGY (TAMADDUN NURI JURNALI, 2025)
Digital technologies have been demonstrated to exert a considerable influence on the cognitive development of Generation Alpha, presenting novel opportunities for learning. However, when utilised excessively, these technologies have been observed to contribute to a reduction in attention span and diminished cognitive flexibility. The present study examines the Trail Making Test (TMT) as a neuropsychological diagnostic tool within the educational environment.